2006
DOI: 10.1210/en.2005-1669
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic Acid Damage and Spontaneous Mutagenesis in the Thyroid Gland of Rats and Mice

Abstract: Thyroid tumors are a frequent finding not only in iodine-deficient regions. They are predominantly characterized by somatic genetic changes (e.g. point mutations or rearrangements). Because slow thyroid proliferation is a apparent contradiction to a high frequency of tumor initiation, we characterized mutational events in thyroid. First we studied the frequency of certain base exchanges in somatic TSH receptor (TSHR) mutations and determined the spontaneous mutation rate in thyroid and liver. Then we applied d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 43 publications
0
47
0
1
Order By: Relevance
“…For many years, H 2 O 2 , considered a DNA genotoxic agent, was suspected to play a mutagenic role in the thyroid gland and to be responsible for the thyroid nodules that were frequently found (24). Several observations strengthen this hypothesis: in mice, the spontaneous mutation frequency is higher in the thyroid gland than in any other organ (25), somatic mutations of the TSH receptor are frequent in human thyroid tissue (24), and thyroid glands of mice transgenic for the mutant a 1B -adrenergic receptor (Tg-a 1B AR mice) that have increased H 2 O 2 generation develop malignant nodules with a high frequency (26). H 2 O 2 causes DNA damage, such as guanine oxidation, single-strand breaks and DSBs leading to mutagenesis and genomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, H 2 O 2 , considered a DNA genotoxic agent, was suspected to play a mutagenic role in the thyroid gland and to be responsible for the thyroid nodules that were frequently found (24). Several observations strengthen this hypothesis: in mice, the spontaneous mutation frequency is higher in the thyroid gland than in any other organ (25), somatic mutations of the TSH receptor are frequent in human thyroid tissue (24), and thyroid glands of mice transgenic for the mutant a 1B -adrenergic receptor (Tg-a 1B AR mice) that have increased H 2 O 2 generation develop malignant nodules with a high frequency (26). H 2 O 2 causes DNA damage, such as guanine oxidation, single-strand breaks and DSBs leading to mutagenesis and genomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…Maier et al (2006) showed that the rat thyroid gland has a high level of DNA oxidative damage in comparison with other tissues, such as liver, spleen, and lung, indicating that the high frequency of somatic mutations and tumor initiation found in this organ is due to the oxidative environment that thyroid cells are subjected to during their long lives (Maier et al 2006 In fact, any disturbance in ROS generation or consumption will promote ROS accumulation that can contribute to thyroid dysfunction. In this context, it is important to note that the site of ROS formation is closely linked to the type and extent of the damage.…”
Section: Ros and Thyroid Pathophysiologymentioning
confidence: 99%
“…However, tissues with a high cell turnover are more sensitive to mutagenesis and other molecular mechanisms that initiate tumour formation, whereas in resting tissues such as the thyroid gland, these mechanisms are less operative. To explain this discrepancy, it has been suggested that free radicals resulting from reactive oxygen species in the thyroid gland generate mutations more frequently (Maier et al 2006).…”
Section: Introductionmentioning
confidence: 99%